2016
DOI: 10.1136/openhrt-2016-000439
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc score, left atrial size and atrial fibrillation as stroke risk factors in the Tromsø Study

Abstract: ObjectiveCHA2DS2-VASc score, left atrial (LA) size and atrial fibrillation (AF) have individually been associated with stroke risk. Our aim was to investigate the predictive ability of combinations of these factors for the odds of incident stroke in a population-based cohort study.MethodsWe followed 2844 participants from the Tromsø Study from 1994 to 2012. Information on LA size and CHA2DS2-VASc score (age, sex, congestive heart failure, hypertension, vascular disease, stroke and diabetes) were obtained at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
(19 reference statements)
1
15
0
1
Order By: Relevance
“…17 Finally, ECG-defined left atrial abnormalities and left atrial enlargement have been shown to be associated with ischemic stroke, independent of AF. 11,18,19 The principal strengths of our study include a prospective community-based investigation with meticulous physician-adjudication of ischemic stroke, including classification of thrombotic and embolic stroke. Other strengths include inclusion of community non-white participants, extensive measurement of covariates, and large number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…17 Finally, ECG-defined left atrial abnormalities and left atrial enlargement have been shown to be associated with ischemic stroke, independent of AF. 11,18,19 The principal strengths of our study include a prospective community-based investigation with meticulous physician-adjudication of ischemic stroke, including classification of thrombotic and embolic stroke. Other strengths include inclusion of community non-white participants, extensive measurement of covariates, and large number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that an increase in left atrial diameter increases the incidence [20][21][22][23][24], recurrence, and the frequency of AF, parallel to an increase in the risk of stroke [23]. There is an increase in interstitial fibrosis within the atrial wall in HF, causing impaired conduction, which is the substrate for AF [25].…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography was performed by two cardiologists on a random subsample ( n = 1722) in Tromsø 5 , using the standard apical and parasternal long‐ and short‐axis views. Standard two‐dimensional guided M‐mode registrations of anteroposterior LA size, internal dimensions of the left ventricle and wall thickness of the septum and posterior wall were made.…”
Section: Methodsmentioning
confidence: 99%
“…The CHA 2 DS 2 ‐VASc score estimates stroke risk in patients with non‐anticoagulated AF by combining risk factors for stroke. Based on data from the Tromsø Study, we have previously shown that adding left atrial (LA) size to an elevated CHA 2 DS 2 ‐VASc score provided additional stratification of stroke risk . In this study, we aimed to investigate the association between AF and cognitive function in a population study with 6 years of follow‐up of stroke‐free women and men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation